ChemInform Abstract: Elucidation of Inorganic Reaction Mechanisms in Ionic Liquids: The Important Role of Solvent Donor and Acceptor Properties. Issue 50 (16th December 2014) - Schmeisser, Matthias; van Eldik, Rudi
Abstract Review: 136 refs.